PENGARUH PENGGUNAAN EMOJI WHATSAPP TERHADAP KEPUASAN REMAJA KOTA DENPASAR DALAM MENYAMPAIKAN PESAN - wibisono, aldilah tri ayu; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica; Damasemil, Calvin (E-Jurnal Medium, 2023)
Emojis are picture or digital icon size small used for express ideas, emotions, and feeling in communication electronics. Whatsapp as wrong one platform communication electronics, of course no miss from use emojis. Use of emojis on application whatsapp is wrong one part from use a medium. According to Palmgreen (Kriyantono,2010: 211), satisfaction use or gratification obtained (GO) is real satisfaction obtained audience after consuming a certain medium . Destination from study this is for to find out how the influence of the use of WhatsApp emoji on the satisfaction of Denpasar City teenagers in conveying messages Study this use method study quantitative with type research associative and use theory uses and gratifications . Study this also involving 140 teenagers from Denpasar City aged 18-25 years. Results study this show usage emoticon on application whatsapp have influence positive and significant to satisfaction Denpasar City youth in convey message. When use whatsapp emojis increase so satisfaction Denpasar City youth in convey message also will the more increase.